Peningkatan Pemahaman dan Kewaspadaan Masyarakat akan Penyakit Arteri Perifer - Donatila Mano S; Agnes Marcella; Yohanes Firmansyah; Alexander Halim Santoso (Institut Teknologi dan Bisnis Semarang, 2023)
Peripheral Arterial disease is a condition in which the peripheral arteries carrying blood to the extremities of the body, such as the feet and hands, become narrowed or blocked due to the large amount of atherosclerotic plaque. The effects of this disease include pain, cramps, difficulty walking, and decreased quality of life. Peripheral artery disease also increases the risk of serious complications such as poorly healing wounds, gangrene, infection and even amputation. In addition, peripheral artery disease can be a sign of more extensive blood vessel disease, such as coronary heart disease or stroke. Therefore, early attention, appropriate treatment, and healthy lifestyle changes are very important to reduce the negative effects of peripheral arterial disease. This community service activity was carried out at the Kalam Kudus Foundation on June 9, 2023. All participants received education and physical care related to peripheral vascular disease. The results of the physical examination revealed that there were 8 (15.4%) respondents with suspected peripheral arterial disease (ABI <0.9) and 4 (7.7%) respondents with suspected vascular calcification (ABI > 1.3). Community Education and Physical Examination with Ankle-Brachial Index (ABI) is an important activity in the prevention and management of peripheral arterial disease. Through community outreach, awareness about peripheral arterial disease can be increased, early symptoms can be identified, and preventive measures can be stepped up. Meanwhile, physical examination with ABI helps detect this disease early, allows timely intervention, and reduces the risk of serious complications. Through the combination of these two approaches, we can increase public understanding, reduce the risk of developing peripheral arterial disease, and improve the quality of life of individuals affected by this disease.